The role of small and medium-sized businesses in the economic development of the country ("Journal "U". Economy. Management. Finance.", 2025)
This article raises the problem of the development of small and medium-sized enterprises in the modern realities of the country. The criteria used to determine the form of business are given, and the directions of SME development in the USA and China are outlined. The problems faced by business are revealed and government support measures are presented to solve them.
Keywords: enterprise; small and medium business; government support; sanctions